Inherent photon energy recycling effects in the up-converted delayed luminescence dynamics of poly(fluorene)-Pt(II)octaethyl porphyrin blends - Keivanidis, Panagiotis E.; Baluschev, Stanislav B.; Lieser, Günter; Wegner, Gerhard (My University, 2009)
We present results of steady-state and transient photoluminescence studies of molecularly doped poly(fluorene) films. We study blends with increasing content of the triplet emitter (2,3,7,8,12,13,17,18-octaethyl-porphyrinato)Pt(II) (PtOEP) when dispersed in the polymeric poly(fluorene) matrix of the poly[9,9-di-(2-ethylhexyl)-fluorenyl-2,7-diyl] (PF26) derivative. We carry out a unified study of the photophysical reactions that are involved in the energy transfer processes in this system by probing the three luminescence processes of a) PF26 fluorescence, b) triplet-triplet annihilation (TTA) induced up-converted PF26 delayed fluorescence and c) PtOEP phosphorescence. With increasing PtOEP content, the process of photon energy recycling in the PF26:PtOEP system is manifested from the quenching of the TTA-induced up-converted PF26 delayed fluorescence and it is rationalized with the use of Forster theory of resonant energy transfer. Based on the combined results of the photophysical and the transmission electron microscopy characterization of the as-spun PF26:PtOEP films, we determine the onset of PtOEP aggregation at 2-3 wt % PtOEP content. The analysis of the photophysical data is based on the use of modified Stern-Volmer photokinetic models that are appropriate for the solid state. A static component in the PL quenching of PF26 is revealed for PtOEP contents below 2 wt %. The modified Stern-Volmer kinetic scheme further suggests that co-aggregation effects between PF26 and PtOEP are operative with an association constant of ground state complex formation k(bind) approximately 15-17 M(-1). The involvement of the ground state heterospecies in the TTA-mediated PF26 up-converted luminescence is discussed. The participation of an electron-exchange step, in the excited state energy transfer pathway between PtOEP and PF26, is proposed for the activation mechanism of the PF26 up-converted fluorescence.
Keywords: Aggregation; Delayed fluorescence; Energy transfer; Photochemistry; Triplet–triplet annihilation